Multifunctional Carbon Dots Derived from Human Hair for Fast Healing Wounds Together with Oleogels - Xiaofeng Shi; Qianli Ma; Xinlin Jia; Zhaofan Wu; Chaohong Yu; Tian Gao; Wei Xu; Zhaonan Sun; Jingwei Zhang; Huanming Xiong; Yuanqing Mao (Small Structures)
In the complex process of wound healing, oleogels (OG) are suitable as the primary component of dressing materials, but they cannot meet the diverse requirements at different healing stages. In this study, a new kind of carbon dots (CrCi‐CDs) prepared by carbonizing human hair, exhibits excellent hemostatic, antibacterial, anti‐inflammatory, and pro‐angiogenic properties and thus supports the various stages of wound healing effectively. Such CrCi‐CDs are incorporated into OG to produce a CrCi‐CD/OG composite material with enhanced multifunctional capabilities, significantly outperforming OG alone. Various experiments in vitro and in vivo confirm that the CrCi‐CDs/OG can rapidly achieve hemostasis at the initial stage of wound formation, subsequently inhibit bacterial proliferation and biofilm formation, improve the complex microenvironment surrounding the wound, and promote neovascularization, ultimately accelerating the wound repair.